Application of Range of Motion (ROM) in Mr. H with Physical Mobility Impairment in Non-Hemorrhagic Stroke Patients - Putri Maharani, Audita; Setyo Dwi Andhini, Citra (INDOGENIUS, 2025)
Background & Objective: Ischemic stroke or non-hemorrhagic stroke is a condition that occurs due to a blockage in the blood vessels of the brain, thereby disrupting blood flow to the brain, either partially or completely. This study aims to evaluate nursing care with the application of Range of Motion (ROM) intervention in non-hemorrhagic stroke patients who experience physical mobility impairment. Method: The method used was a case study of one patient at RSD Gunung Jati Cirebon. Data collection techniques included interviews (anamnesis), physical assessment, direct observation, and documentation. Result: Nursing care was provided over three days, during which the patient initially complained of pain and limited movement in the left extremity. Mobilization interventions in the form of ROM exercises based on Evidence-Based Nursing (EBN) were administered for three consecutive days, with each session lasting 25 minutes and each movement repeated. Evaluation results showed an improvement in physical mobility from a score of 2 to 3. Conclusion: Thus, ROM exercises have been proven effective in improving mobility in patients with physical mobility impairments due to non-hemorrhagic stroke.